Stress Testing Financial Systems - Jones, Matthew (Pamphlet Series; Pamphlet Series, No., 2004)
Stress testing is becoming a widely used tool to assess potential vulnerabilities in a financial system. This booklet is intended to answer some of the basic questions that may arise as part of the process of stress testing. The pamphlet begins with a discussion of stress testing in a financial system context, highlighting some of the differences between stress tests of systems and of individual portfolios. The booklet provides an overview of the process itself, from identifying vulnerabilities, to constructing scenarios, to interpreting the results. The experience of the IMF in conducting stress testing as part of the Financial Sector Assessment Program (FSAP) is also discussed.